From something to nothing : jewish mysticism in contemporary Canadian Jewish studies (Cambridge Scholars Publishing, 2018)
Jewish mysticism approaches God as no-thing or nothing, reflecting Judaism's traditional identification of God as incorporeal. Whereas technical philosophical language often employed to discuss Jewish mysticism has a tendency to ward off otherwise interested readers, this study sufficiently breaks down the technical language of Jewish mysticism in its various expressions to allow a beginner to benefit from what may otherwise be indescribable and only approached by consideration of what is not rather than what is. Integral to the title, From Something to Nothing, is the concept that God cannot b.